2021
DOI: 10.1101/2021.06.02.446747
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deep-rooted plant species recruit distinct bacterial communities in 3 m deep subsoil

Abstract: Deep-rooted plants can obtain water and nutrients from the subsurface, making them more resilient to climatic changes such as drought. In addition, the deeper root network also allow the plants to recruit bacteria from a larger reservoir in the soil. These bacteria might contribute to nutrient acquisition and provide other plant beneficial traits to the plant. However, the deep rhizosphere communities' compositions and their assembly dynamics are unknown. Here, we show, using three perennial crops, Kernza, luc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
(63 reference statements)
0
1
0
Order By: Relevance
“…On the one side, halophytes' microbiome may change the ion composition of soil around the root through microbial metabolism to further affect the adaptability against adversity such as hypersaline stress. On the other side, the root network also allows halophytes to recruit distinct bacteria from a larger soil microbial reservoir to construct microbiomes to benefit themselves [59]. Li et al confirmed the critical role of salt-induced root-derived bacteria (RDB) in enhancing plant adaptability to salt stress by measuring the composition and variation in the rhizosphere and endophyte bacteria of salt-sensitive (SS) and salt-resistant (SR) plants under soil conditions with or without salinity [60].…”
Section: Discussionmentioning
confidence: 99%
“…On the one side, halophytes' microbiome may change the ion composition of soil around the root through microbial metabolism to further affect the adaptability against adversity such as hypersaline stress. On the other side, the root network also allows halophytes to recruit distinct bacteria from a larger soil microbial reservoir to construct microbiomes to benefit themselves [59]. Li et al confirmed the critical role of salt-induced root-derived bacteria (RDB) in enhancing plant adaptability to salt stress by measuring the composition and variation in the rhizosphere and endophyte bacteria of salt-sensitive (SS) and salt-resistant (SR) plants under soil conditions with or without salinity [60].…”
Section: Discussionmentioning
confidence: 99%